AWS Certified Database – Specialty (DBS-C01) Cert Prep: 1 Introduction and Services. - Carpenter, Tom (linkedin.com, 2020)
Review fundamental database concepts—and the different database services offered by AWS—as you prepare to take and pass the AWS Certified Database – Specialty (DBS-C01) exam.